Položaj civilnega prebivalstva v Prekmurju ob koncu vojne - Kerec, Darja (Studia Historica Slovenica, 2016)
This paper describes the situation of the civilian population in Prekmurje in the weeks and months at the end of the war. The specifics of the liberation of Prekmurje with the arrival of the Red Army was at that time also reflected in the everyday life of the locals who, despite a difficult financial and social situation, had to assist soldiers by collection campaigns and blood donation as ordered by the local authorities. Then came a time of reconstruction, which engulfed all classes of the civilian population. Outside official activity smuggling had been established, because in spite of the establishment of cooperatives there was a shortage of goods. As a result, dissatisfaction spread among the people, as well as criticism of the situation in the region that offered shelter and recuperation to the soldiers of the Red Army.
Keywords: 1945; druga svetovna vojna; prebivalstvo; Prekmurje; Slovenija; svetovna vojna 1939-1945